Jurisprudence as a Legal Resource in Indonesia to Handle Cases in Society - Sri Rizki Hayaty; Dedi Iskandar; Nelvitia Purba (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2021)
Jurispudence is a customary carried out by judges to follow the verdict of judges who have the power of law to exist for the same case. The high court’s decision is considered to contain the main points of thought about legal issues that occur in the community. Jurisprudence is the decisions of judges made by courts that already have a fixed legal force on the case that is handled based on the decision of the previous judge on the same case and this is justified by the Supreme Court (SC) as the Court of Cassation, or the Supreme Court itself which already has permanent legal force. So here the judge not only applies the law, but the judge can also and is able to form a law (judge made law). Especially if the rules contained in the law are unclear, or the existing laws are not in accordance with the current circumstances and the law does not regulate the problems at hand. Research methods in this writing was to use normative methods or literature studies where this research was to use various secondary data such as laws and regulations, court decisions, legal theories, and could be the opinions of scholars. It can be argued that this jurisprudence applies to the principle in law that judges should not refuse to adjudicate cases brought against it. Judges as law enforcement and justice are obliged to judge, follow and understand the legal values that live in society, then in handling cases judges can do: apply in concreto existing legal rules (in abstracto) and apply since before and seek for the rules of law based on legal values that live in society in the process of resolving cases that are handled